Characteristics of the Board of Commissioners, Directors, and Financial Distress - Sari, Wa Ode Nurmila; Setiawan, Doddy (Universitas Negeri Semarang, 2024)
Purpose : The purpose of this study is to determine whether the quality of the board of directors and commissioners affects financial distress. These characteristics are reviewed based on the percentage of female commissioners, independent commissioners, size of the board of commissioners, education of the board of commissioners, percentage of female directors, percentage of independent directors, education of directors, and size of the board of directors. Method : The study used a sample of 222 Indonesian State-Owned Enterprises from 2016 to 2021. The data analysis technique used was logistic regression analysis. Findings : First, the data empirically demonstrates that the percentage of female commissioners, independent commissioners, educational policy, and board size all positively impact financial distress. Second, financial trouble is unaffected by the percentage of female directors, independent directors, the education of the board of commissioners, and the size of the board. Novelty : The research sample is where this study differs from other research. Prior research only looked at one industry of companies experiencing financial trouble in wealthy nations. The State-Owned Enterprises industry in Indonesia is the main subject of this study.